KUALITAS LAYANAN JUMBO FRAME PADA PROSES TRANSFER DATA FAKULTAS TEKNIK KAMPUS SUDIRMAN UNIVERSITAS UDAYANA - Kresnadi Putra, I Putu Eka Giri Setya; Sukadarmika, Gede; Wirastuti, Ni Made A E D (Jurnal SPEKTRUM, 2019)
The development of network technology is increasingly growing. The high amount of digital data passed on computer networks is currently influenced by the increasing use and need of the era of digitalization. Therefore it is required reliable network conditions and can provide time efficiency. This final project analyzed the effect of jumbo frame service quality on data transfer process. The experiment conducted int two types frame network that is normal frame and jumbo frame network. It is found that the best average of frame size is 5000 bytes. In term of QoS parameters obtained that for packet loss ranges from 0.01% to 1.22%, delay ranges from 94 to 400 seconds, and throughput ranges from 20 to 50Mbps. Compared with the frame size of 9000 bytes with packet loss value of more than 2%.